On the Maximum SC Index of Chemical Unicyclic Graphs - Hui-Yan Cheng; Lei Chen; Sattar Alyar (Journal of Mathematics)
The sum-connectivity SC index of a graph G is defined as SCG=∑μν∈EG1/Θμ+Θν, where Θμ denotes the vertex degree of μ in G. In this paper, the fourth largest value of SC index for the chemical unicyclic graphs of order n≥7 is determined.